(untitled) (World Bulletin of Social Sciences, 2026)
This article is devoted to the history of trade relations and transit connections of the countries of the region through the Amu Darya crossings in the late 19th century. It is also analyzed that the Amu Darya crossings, which are of great economic and political importance, have long been a means of uniting peoples as bridges connecting the intersecting land and waterways of the region.